2007
DOI: 10.1007/bf02893504
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the prognostic role of tissue eosinophil and mast cells in Hodgkin’s lymphoma

Abstract: The composition of reactive cell populations, which constitute the majority of tumor load in Hodgkin's lymphoma (HL), can influence the prognosis of the disease. Besides widely accepted and applied prognostic scores, the authors evaluate biological factors that may have a prognostic impact. Previous data indicate that the rate of eosinophils and mast cells in the reactive cell population, determined already at diagnosis, can be used for this purpose. Histological samples from 104 patients with HL with an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
19
2
3
Order By: Relevance
“…Recent studies suggest that recruited inflammatory cells may provide essential feedback signals to the neoplastic cells and thus represent important lymphoma/host microenvironment modulators [1][2][3][4][5]11]. The most convincing in vivo observation in support of this hypothesis is that provided by Biggar et al [15], who showed that HIV+ patients with low CD4 + cell counts had a significantly lower risk of developing classical Hodgkin lymphoma compared with those with high CD4 + cell counts.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recent studies suggest that recruited inflammatory cells may provide essential feedback signals to the neoplastic cells and thus represent important lymphoma/host microenvironment modulators [1][2][3][4][5]11]. The most convincing in vivo observation in support of this hypothesis is that provided by Biggar et al [15], who showed that HIV+ patients with low CD4 + cell counts had a significantly lower risk of developing classical Hodgkin lymphoma compared with those with high CD4 + cell counts.…”
Section: Discussionmentioning
confidence: 83%
“…One study has shown that patients with high levels of Granzyme B and T-cell restricted antigen-1 (TIA-1)+ cells have an unfavorable clinical course [2]. Other studies on the role of mast cells in classical Hodgkin lymphoma suggest that mast cells are associated with poorer overall survival or that higher mast cell infiltration results in lower relapse-free survival [3,4]. FOXP3 is a marker for a subset of CD4 + CD25 + regulatory T cells (Tregs) in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 98%
“…Keresztes et al reported that mast cell infiltration was similar in MCCHL and NSCHL. 28 On the other hand, some authors reported that NSCHL correlated with higher numbers of tumor-infiltrating mast cells, compared with non-NSCHL. [29][30][31] Immunodeficient NOD/SCID mice inoculated with both mast cells and human HRS cells grew tumors with a more marked fibrotic component, compared with tumors in mice inoculated with HRS cells alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Molin et al . found high numbers of mast cells to be associated with poor prognosis in Hodgkin's lymphoma, although this finding was not confirmed by a separate group . In an earlier study, Molin and co‐authors had shown that mast cells are able to stimulate HRS cell lines in vitro via CD30 ligand–CD30 interaction.…”
mentioning
confidence: 92%
“…In cHL, high numbers of intratumoral mast cells have been shown to be associated with nodular sclerosis (NS) subtype histology (7), while a more recent study found somewhat lower numbers of mast cells in EBV-positive tumours, compared to EBVnegative tumours (8). In addition, Molin et al (7) found high numbers of mast cells to be associated with poor prognosis in Hodgkin's lymphoma, although this finding was not confirmed by a separate group (9). In an earlier study, Molin and co-authors had shown that mast cells are able to stimulate HRS cell lines in vitro via CD30 ligand-CD30 interaction.…”
mentioning
confidence: 98%